(untitled) (Eurasian Medical Research Periodical, 2022)
The article presents the results of studies of small amounts of unknown substances in a mixture on carrier objects by gas-liquid chromatography with a mass spectrometric detector. It was established: the presence of unsaturated and unsaturated fatty acids, diphenhydramine, as well as narcotic drugs - codeine and thebaine in the examined syringe and on cotton swabs; retention time, molecular and fragmentation ions, their intensity, individuality of fragmentation of molecules of diphenhydramine, codeine and thebaine.